2022
DOI: 10.4103/njcp.njcp_1985_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eye health in children with type 1 diabetes mellitus and celiac disease

Abstract: Background: Pediatric celiac disease (CeD) and type 1 diabetes mellitus (T1DM) have well established effects on eye health but comorbid effect is not known. Aim: To evaluate the eye health of children with T1DM and CeD to predict microvascular retinal pathologies by diagnosis of probable intraocular pressure increase which is an important glaucoma trigger. Patients and Methods: In this case-controlled study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The mean IOP was also higher in the T1DM group than in the control group. Dereci et al [ 13 ] and Akil et al [ 15 ] reported similar findings in their studies. This can potentially be attributed to persistent hyperglycemia, which is thought to cause excessive extracellular matrix synthesis in the trabecular meshwork, sequentially causing outflow obstruction of the aqueous humor in the anterior segment of the eye and elevating intraocular pressure [ 17 ].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The mean IOP was also higher in the T1DM group than in the control group. Dereci et al [ 13 ] and Akil et al [ 15 ] reported similar findings in their studies. This can potentially be attributed to persistent hyperglycemia, which is thought to cause excessive extracellular matrix synthesis in the trabecular meshwork, sequentially causing outflow obstruction of the aqueous humor in the anterior segment of the eye and elevating intraocular pressure [ 17 ].…”
Section: Discussionsupporting
confidence: 74%
“…In addition, it is thought that the accumulation of reactive oxygen species, advanced glycated end products, and growth factors induce the activation and proliferation of corneal stromal keratocytes [16]. In contrast, studies by Dereci et al [13] and Wang et al [14] report lower mean CCT values in children with T1DM than the control group in their study. Wang et al [14] argue that low CCT values were due to apoptosis and cell death resulting from hyperglycemia.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations